OP06 Socio-demographic inequalities in cardiovascular risk management and early detection of vascular conditions by the nhs health check: a difference-in-differences matching analysis. (2nd September 2017) - Chang, K; Lee, JT; Vamos, E; Palladino, R; Soljak, M; Majeed, A; Millett, C
Abstract : Background: England's National Health Service (NHS) Health Check is a nationwide cardiovascular risk assessment and management programme implemented with aims to prevent cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM) and chronic kidney disease, as well as to reduce inequalities in health. We aimed to compare the impact of the NHS Health Check on: i) Early detection of vascular conditions among population subgroups of age, sex, ethnicity and deprivation; and ii) The management of cardiovascular risk among high-risk population subgroups of age, sex, and deprivation. Methods: We obtained retrospective electronic medical records from the Clinical Practice Research Datalink for a randomly selected sample of 1 38 788 patients aged 40–74 years, without known CVD or diabetes, and were registered with 462 English general practices between 2009 and 2013. We estimated programme impact for each subgroup using a difference-in-differences matching analysis that compared changes in outcome over time and between Health Check attendees and non-attendees. Results: 21.4% (29, 672/138, 788) of the study population attended a Health Check. The programme was associated with increased detection of hypertension and T2DM among Health Check attendees. A significantly greater number of hypertension and T2DM incident cases were detected in male than female attendees (e.g. an additional 4.02%, 95% CI: 3.65% to 4.39%, and 2.08%, 1.81% to 2.35% male and female attendees were detected with hypertension respectively). A significantly greater number of T2DM incident cases were detected among attendees living in the most deprived area (1.60%, 1.23% to 1.97%) compared with those living in the least deprived area (0.79%, 0.52% to 1.06%). The programme was associated with significant reductions in 10 year CVD risk scores, total cholesterol and systolic blood pressure while statin prescribing increased among high-risk attendees. However, no major differences in programme impact on cardiovascular risk management were observed between subgroups (e.g. programme impact on 10 year CVD risk score was −1.13%, −1.48% to −0.78% in male and −1.53%, −2.36% to −0.71% in female attendees). Conclusion: The NHS Health Check may have narrowed inequalities in the diagnosis of hypertension and T2DM but inequalities in the management of CVD risk remained unchanged. Proactive strategies may be required to address known inequalities in CVD outcomes.